Post-harvest technologies applied to edible flowers: a review - Fernandes, Luana (2019)
This review intends to summarize the current knowledge on the post-harvest technologies applied to edible flowers, to help producers to increase their market share and to inform consumers on the technologies that are available to maintain edible flowers’ quality and safety. Emerging post-harvest technologies as High Hydrostatic Pressure (HHP) or irradiation have given good results. Freeze- or vacuum-drying has shown to be highly effective in the preservation of flowers’ bioactive compounds in comparison with classical drying approaches. While osmotic dehydration is already in use, the application of edible coatings and films can be a healthier alternative, without increasing solute contents.